(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the current status of lipid metabolism disorders in workers at Detech E-Scooters and Motorcycle Company Limited in 2023. Subject and methods: The study was conducted with 258 workers at Detech E-Scooters and Motorcycle Company Limited. Data was collected through retrospective medical records and health examinations of workers. Results: The rate of lipid metabolism disorders in workers was 36%, of which 18.2% had simple lipid metabolism disorders and 17.8% had mixed lipid metabolism disorders. The workers were male, over 45 years old, and overweight and obesity were risk associated factors with lipid metabolism disorders in workers with p < 0,05. Conclusion: The incidence of lipid metabolism disorders is relatively high, including both pure and mixed lipid metabolism disorders. Some factors related to lipid metabolism disorders of workers are male gender, over 45 years old and overweight and obese.